Representation of Gender Identity in Dean Atta’s The Black Flamingo (Sastra Inggris UNPAM, 2025)
The background of this study is based on the concept of gender identity as a social and interactive process through which individuals recognize themselves as male or female. This study aims to analyze how gender identity is represented in The Black Flamingo by Dean Atta and to examine how the main character navigates and negotiates his gender identity throughout the novel. A qualitative method was employed, and data were collected through a narrative analysis of the novel. The analysis applied Judith Butler’s (1990) theory of gender performativity to explore how the text portrays issues of gender and identity. The results indicate that the protagonist reflects his gender identity through expressions of both masculinity and femininity. The study also reveals how the character deals with gender identity as both a performative and normative construct. Overall, the findings demonstrate that the character embodies multiple aspects of gender identity, alternating between feminine and masculine traits, and ultimately resists traditional gender norms to assert his authentic self.